(untitled) (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2021)
The study investigates the novel The Wandering Falcon (2011) by Jamil Ahmad in the milieu of feminist approach. It qualitatively explores the text for the representation of women: the treatment of women by men, and their position in the patriarchal society. The novel is analysed by employing De-Beauvoir’s (1949) feministic philosophical approach in The Second Sex. This research explores the way power is exercised over women in the novel and the suppression of women by men plays as an instrument of transmission of customs and traditions. This research is to explore the novel from a feministic perspective to unveil the hidden realities in the novel regarding women to find out what sort of oppression is faced by women in the novel and to explore the general problems of women in the novel. It is found that in the context of the novel, women are treated unjustly by men. They are deprived of their rights and are taken as commodities in the patriarchal society. Women are stereotypically presented as having no identity, no freedom, and no voice of their own. Being treated as objects and things to be traded by men, women in the novel are found facing domestic violence, sexual objectification, and extra judicial killings.